Government Policy and Farmland Markets: Implications of the New Economy--Part 2 - Charles B. Moss; Andrew Schmitz; Barry K. Goodwin; Ashok K. Mishra (EDIS)
This is EDIS document FE358, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published October 2002.